All-solid-state alkali metal battery and preparation method and application thereof
By using ultrasonic welding technology in all-solid alkali metal batteries to weld alkali metal foil and solid electrolyte at room temperature, the problem of poor contact performance of solid-solid interface is solved, and low interface impedance and stability are improved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202110020566.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-01-07
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-01-07
AI Technical Summary
All-solid alkali metal batteries based on oxide solid electrolytes have poor physical contact performance between the solid-solid interface between the electrolyte and the metal electrode, resulting in large interface impedance and difficult to work properly. The preparation process of common methods is complicated and is not suitable for large-scale production.
Ultrasonic welding method is used to construct a tight bonding interface of the negative electrode/solid electrolyte in an alkali metal all-solid state battery. By applying ultrasonic welding of the alkali metal foil and the solid electrolyte at room temperature, the interface impedance is reduced and uniform deposition is achieved.
The low interface impedance between alkali metal foil and solid electrolyte is achieved, the cycle stability and rate performance of all solid alkali metal batteries are improved, the preparation process is simplified, and it is suitable for large-scale production.
Smart Images

Figure CN114497708B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of all-solid-state alkali metal batteries, and specifically relates to an all-solid-state alkali metal battery and a preparation method and application thereof. Background Art
[0002] All-solid-state alkali metal batteries based on oxide solid electrolytes have attracted widespread attention due to their high energy density and superior safety performance. Oxide solid electrolytes have high room temperature ionic conductivity (10 -4 ~10 -3 S cm -1 ), wide electrochemical window, which makes it more suitable for cathode materials with higher working voltage. In addition, oxide solid electrolytes have high mechanical strength and can effectively alleviate and inhibit the growth of dendrites of alkali metal negative electrodes. In addition, since they replace flammable and explosive organic electrolytes, oxide solid electrolytes also have superior safety performance, making the practical application of alkali metal batteries possible.
[0003] However, all-solid-state alkali metal batteries based on oxide solid electrolytes also have shortcomings that cannot be ignored. Due to the poor physical contact performance of the solid-solid interface between the electrolyte and the metal electrode, a huge interface impedance is generated, making it almost impossible for all-solid-state batteries to work normally at room temperature. In addition, since the effective contact area of the solid-solid interface contact is too small, the alkali metal cannot be evenly deposited on the surface of the solid electrolyte, and then forms dendrites, which eventually penetrate the electrolyte and cause the battery to short-circuit.
[0004] At present, some technologies have been reported in the literature to solve this problem. For example, the contact between the alkali metal anode and the oxide electrolyte is improved by melting the alkali metal anode, but it requires a higher heating temperature, which is not conducive to practical application; and high-temperature melting will cause side reactions between the metal anode and the oxide solid electrolyte that strengthens the reduction. In addition, a buffer layer can be constructed between the solid electrolyte and the alkali metal anode to reduce the interface impedance and induce the uniform deposition of alkali metals, such as Al2O3, TiO2, SiO2, graphite, etc. However, most of the above methods use chemical vapor deposition, atomic layer deposition, magnetron sputtering and other methods, and the preparation process is complicated and expensive, which is not suitable for large-scale production. Summary of the invention
[0005] In view of the deficiencies in the prior art, an object of the present invention is to provide an all-solid-state alkali metal battery.
[0006] Another object of the present invention is to provide a method for preparing the above-mentioned all-solid-state alkali metal battery.
[0007] Another object of the present invention is to provide an application of an ultrasonic welding method in constructing a close bonding interface between anode and solid electrolyte in an alkali metal all-solid-state battery.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] An all-solid-state alkali metal battery comprises a solid electrolyte, a positive electrode and a negative electrode, wherein the negative electrode is an alkali metal foil and is connected to one side of the solid electrolyte by ultrasonic welding.
[0010] In the above technical solution, the alkali metal foil is a lithium metal foil, a sodium metal foil or a potassium metal foil, and the all-solid-state alkali metal battery is an all-solid-state lithium metal battery, an all-solid-state sodium metal battery or an all-solid-state potassium metal battery.
[0011] In the above technical solution, the thickness of the alkali metal foil is 0.1-0.5 mm, preferably 0.15 mm.
[0012] In the above technical solution, the solid electrolyte is a polymer solid electrolyte, a sulfide solid electrolyte or an oxide solid electrolyte, preferably an oxide solid electrolyte.
[0013] In the above technical solution, the thickness of the solid electrolyte is 0.4 to 2 mm, preferably 0.5 to 1 mm.
[0014] In the above technical solution, the solid electrolyte is Li7La3Zr2O 12 , Na-β"-Al2O3 or Na3Zr2Si2PO 12 .
[0015] The preparation method of the above-mentioned all-solid-state alkali metal battery includes: welding the alkali metal foil on one side of the solid electrolyte by ultrasonic welding, assembling the solid electrolyte, the positive electrode and the negative electrode into an all-solid-state alkali metal battery, wherein the temperature of the ultrasonic welding is room temperature 20 to 25°C.
[0016] In the above technical solution, the welding time of the ultrasonic welding is 15 to 60 seconds.
[0017] In the above technical solution, the ultrasonic frequency of the ultrasonic welding is 30 to 80 KHz.
[0018] In the above technical solution, when welding the alkali metal foil on the solid electrolyte: the alkali metal foil is attached to one side of the solid electrolyte, and the ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied.
[0019] The preparation method is used to construct a close interface between the negative electrode and the solid electrolyte in all-solid-state alkali metal batteries.
[0020] The interface constructed by the ultrasonic welding method of the present invention realizes a lower interface impedance between the alkali metal foil and the solid electrolyte, constructs a stable interface where the alkali metal foil can be uniformly deposited, and improves the cycle stability and rate performance of the all-solid-state alkali metal battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The sodium metal foil obtained in Example 1 and Li7La3Zr2O 12 SEM and EDX images of the solid electrolyte ultrasonic welding interface, where (a) is the SEM image, (b) is the EDX image of the Na element, (c) is the EDX image of the La element, and (d) is the EDX image of the Zr element;
[0022] Figure 2 The lithium metal foil obtained in Example 2 and Li7La3Zr2O 12 SEM and EDX images of the solid electrolyte ultrasonic welding interface, where (a) is the SEM image, (b) is the EDX image of the La element, and (c) is the EDX image of the Zr element;
[0023] Figure 3 The SEM and EDX images of the ultrasonic welding interface between the sodium metal foil and the Na-β"-Al2O3 solid electrolyte obtained in Example 3, wherein (a) is a SEM image, (b) is an EDX image of the Na element, and (c) is an EDX image of the Al element;
[0024] Figure 4 The AC impedance diagram of sodium metal foil / Na-β"-Al2O3 solid electrolyte / sodium metal foil;
[0025] Figure 5 The SEM and EDX images of the ultrasonic welding interface between the lithium metal foil and the Na-β"-Al2O3 solid electrolyte obtained in Example 4, wherein (a) is a SEM image, (b) is an EDX image of the Na element, and (c) is an EDX image of the Al element;
[0026] Figure 6 The AC impedance diagram of lithium metal foil / Na-β"-Al2O3 solid electrolyte / lithium metal foil;
[0027] Figure 7 The lithium metal foil and Na3Zr2Si2PO4 obtained in Example 5 12 SEM and EDX images of the solid electrolyte ultrasonic welding interface, where (a) is the SEM image, (b) is the EDX image of the Na element, (c) is the EDX image of the Zr element, (d) is the EDX image of the Si element, and (e) is the EDX image of the P element;
[0028] Figure 8Lithium metal foil / Na3Zr2Si2PO 12 AC impedance diagram of solid electrolyte / lithium metal foil;
[0029] Fig. 9 The sodium metal foil and Na3Zr2Si2PO4 obtained in Example 6 12 SEM and EDX images of the solid electrolyte ultrasonic welding interface, where (a) is the SEM image, (b) is the EDX image of the Na element, (c) is the EDX image of the Zr element, (d) is the EDX image of the Si element, and (e) is the EDX image of the P element;
[0030] Fig.10 Sodium metal foil / Na3Zr2Si2PO 12 AC impedance diagram of solid electrolyte / sodium metal foil;
[0031] Fig.11 Sodium metal foil / Na3Zr2Si2PO 12 Solid electrolyte / Na metal foil at 25 °C at 0.1 mA cm -1 Cycle diagram under current density of ;
[0032] Fig.12 Sodium metal foil / Na3Zr2Si2PO 12 Solid electrolyte / Na metal foil at 25 °C at 0.2 mA cm -2 Cycle diagram under current density of ;
[0033] Fig.13 The 1C charge and discharge test diagram of the all-solid-state alkali metal battery at 25°C obtained in Example 7;
[0034] Fig.14 This is a multi-rate charge and discharge test chart of the all-solid-state alkali metal battery obtained in Example 7 at 25°C. DETAILED DESCRIPTION
[0035] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0036] The solid electrolyte is Na3Zr2Si2PO 12 , Preparation of solid electrolyte: Na3Zr2Si2PO4 was synthesized by traditional solid phase method 12Solid electrolyte. Weigh sodium carbonate, zirconium oxide, silicon dioxide and diammonium phosphate. The ratio of sodium in sodium carbonate, zirconium in zirconium oxide, silicon in silicon dioxide and phosphorus in diammonium phosphate is 3:2:2:1 according to the amount of substance. Ball mill at a speed of 1200r / min for 60min, sinter the fully mixed powder at 1100℃ for 12h to obtain a precursor powder. Ball mill the obtained precursor powder at a ball milling speed of 1200r / min, a ball milling time of 60min, and a ball-to-material ratio of 15:1. After drying, press it into an embryo with a size of Φ16mm×1mm. Sinter the obtained embryo at 1200℃ in a muffle furnace for 12h to obtain Na3Zr2Si2PO 12 Structured solid electrolyte.
[0037] Solid electrolyte is Li7La3Zr2O 12 , Preparation of solid electrolyte: Li7La3Zr2O synthesized by traditional solid phase method 12 Solid electrolyte. Lithium hydroxide, lanthanum hydroxide and zirconium oxide were weighed. The ratio of lithium in lithium hydroxide, lanthanum in lanthanum hydroxide and zirconium in zirconium oxide was 7:3:2 according to the amount of substance. Ball milling was performed at a speed of 1200r / min for 60min, with a ball-to-material ratio of 15:1. The fully mixed powder was sintered at 900℃ for 12h to obtain a precursor powder. The obtained precursor powder was ball milled at a ball milling speed of 1200r / min, a ball milling time of 60min, and a ball-to-material ratio of 15:1. After drying, it was pressed into an embryo with a size of Φ16mm×1mm. The obtained embryo was sintered at 1100℃ in a muffle furnace for 9h to obtain Li7La3Zr2O 12 Structured solid electrolyte.
[0038] The solid electrolyte is Na-β"-Al2O3. Preparation of Na-β"-Al2O3 solid electrolyte: Na-β"-Al2O3 solid electrolyte is synthesized by traditional solid phase method. Boehmite, lithium carbonate and sodium carbonate are weighed. According to the amount of substance, the ratio of aluminum in boehmite, lithium in lithium carbonate and sodium in sodium carbonate is 1.67:0.33:0.67. The fully mixed powder is ball milled at a speed of 1200r / min for 60min, and the ball-to-material ratio is 15:1. The powder is sintered at 1250°C for 2h to obtain a precursor powder. The obtained precursor powder is ball milled at a ball milling speed of 1200r / min, a ball milling time of 60min, and a ball-to-material ratio of 15:1. After drying, it is pressed into an embryo with a size of Φ16mm×1mm. The obtained embryo is sintered at 1580°C for 4h in a muffle furnace to obtain a solid electrolyte with a Na-β"-Al2O3 structure.
[0039] The model of SEM test instrument is: Phenom Pro, China
[0040] The model of the AC impedance tester is: CHI760D, China
[0041] The model of the constant current cycle tester is: LANDdt, China
[0042] The interfacial impedance between the alkali metal foil and the solid electrolyte is calculated as:
[0043] 1. A symmetrical cell was constructed according to the blocking electrode / solid electrolyte / blocking electrode structure, and the impedance of the solid electrolyte was determined using electrochemical impedance spectroscopy, which was calculated as A1. The blocking electrode was prepared by gold spraying.
[0044] 2. A symmetrical battery was constructed according to the alkali metal foil / solid electrolyte / alkali metal foil structure, and the total impedance of the symmetrical battery was determined using electrochemical impedance spectroscopy, which was calculated as A2.
[0045] 3. The interface impedance between the solid electrolyte and the alkali metal foil is A3, where A3 = (A2-A1) / 2.
[0046] Example 1
[0047] A method for tightly combining an alkali metal foil with a solid electrolyte, wherein the alkali metal foil is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a sodium metal foil, the thickness of the alkali metal foil is 0.3 mm, and the solid electrolyte is Li7La3Zr2O 12 , the thickness of the solid electrolyte is 1.3 mm.
[0048] The method for tightly combining the alkali metal foil and the solid electrolyte comprises: welding an alkali metal foil on one side of the solid electrolyte by ultrasonic welding, wherein when welding the alkali metal foil on the solid electrolyte: the alkali metal foil is attached to one side of the solid electrolyte, the ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied, the temperature of ultrasonic welding is room temperature 20 to 25°C, the welding time of ultrasonic welding is 15s, and the ultrasonic frequency of ultrasonic welding is 50KHz.
[0049] Figure 1 The sodium metal foil obtained in this example and Li7La3Zr2O 12 SEM image of the solid electrolyte ultrasonic welding interface. It can be seen from the figure that metallic sodium and Li7La3Zr2O 12 The solid electrolytes are tightly bonded to each other.
[0050] Example 2
[0051] A fully solid-state alkali metal battery, which is a fully solid-state lithium metal battery, comprises: a positive electrode shell, a nickel foam (diameter 10 mm), a positive electrode, a solid electrolyte, a negative electrode, a nickel foam (diameter 10 mm) and a negative electrode shell, two nickel foams are respectively installed between the positive electrode and the positive electrode shell and between the negative electrode and the negative electrode shell as current collectors, the positive electrode shell and the negative electrode shell used in packaging are 2032 battery shells, the negative electrode is an alkali metal foil, and the negative electrode is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a lithium metal foil, the thickness of the alkali metal foil is 0.3 mm, and the solid electrolyte is Li7La3Zr2O 12 The thickness of the solid electrolyte is 1.4 mm, and the positive electrode is a LiFePO4 electrode sheet.
[0052] The preparation method of the above-mentioned all-solid-state alkali metal battery includes: welding the alkali metal foil on one side of the solid electrolyte by ultrasonic welding, assembling the positive electrode shell, nickel foam, positive electrode, solid electrolyte, negative electrode, nickel foam and negative electrode shell into an all-solid-state alkali metal battery, wherein, when welding the alkali metal foil on the solid electrolyte: stick the alkali metal foil to one side of the solid electrolyte, hold the ultrasonic tool head against the surface of the alkali metal foil and apply ultrasonic waves, the temperature of ultrasonic welding is room temperature 20-25°C, the welding time of ultrasonic welding is 25s, and the ultrasonic frequency of ultrasonic welding is 50KHz. Electrolyte is dripped between the positive electrode and the solid electrolyte for wetting. The volume of the electrolyte is 7.5μL, and the area of the LiFePO4 electrode plate is 1.1304cm 2 The electrolyte is a mixture of lithium hexafluorophosphate, ethylene carbonate and dimethyl carbonate, the concentration of lithium hexafluorophosphate in the electrolyte is 1 mol / L, and the volume ratio of ethylene carbonate to dimethyl carbonate is 1:1.
[0053] Preparation method of LiFePO4 electrode sheet: mix LiFePO4, conductive carbon black and PVDF in a mass ratio of 8:1:1, and then mix them with NMP solvent to obtain slurry, wherein the mass ratio of LiFePO4, conductive carbon black and PVDF to the mass ratio of NMP is 200:1, apply the mixed slurry on aluminum foil, and vacuum dry it at 80℃ for 24h. Cut it into discs with a diameter of 12mm for standby use to obtain LiFePO4 electrode sheet, wherein the loading amount of LiFePO4 electrode sheet is about 1mg cm -2 .
[0054] Figure 2 The lithium metal foil obtained in this example and Li7La3Zr2O 12 SEM image of the solid electrolyte ultrasonic welding interface. It can be seen from the figure that the metal lithium and Li7La3Zr2O 12 The solid electrolytes are tightly bonded to each other.
[0055] Example 3
[0056] The invention discloses an all-solid-state alkali metal battery, which is an all-solid-state sodium metal battery, comprising: a positive electrode shell, a nickel foam (diameter 10 mm), a positive electrode, a solid electrolyte, a negative electrode, a nickel foam (diameter 10 mm) and a negative electrode shell, wherein two nickel foams are respectively installed between the positive electrode and the positive electrode shell and between the negative electrode and the negative electrode shell as current collectors, the positive electrode shell and the negative electrode shell used in packaging are 2032 battery shells, the negative electrode is an alkali metal foil, and the negative electrode is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a sodium metal foil, the thickness of the alkali metal foil is 0.2 mm, the solid electrolyte is Na-β"-Al2O3, the thickness of the solid electrolyte is 1 mm, and the positive electrode is a Na3V2(PO4)3 electrode sheet.
[0057] The preparation method of the above-mentioned all-solid-state alkali metal battery includes: welding the alkali metal foil on one side of the solid electrolyte by ultrasonic welding, assembling the positive electrode shell, nickel foam, positive electrode, solid electrolyte, negative electrode, nickel foam and negative electrode shell into an all-solid-state alkali metal battery, wherein when welding the alkali metal foil on the solid electrolyte: stick the alkali metal foil to one side of the solid electrolyte, hold the ultrasonic tool head against the surface of the alkali metal foil and apply ultrasonic waves, the ultrasonic welding temperature is room temperature 20-25°C, the ultrasonic welding time is 25s, and the ultrasonic frequency of the ultrasonic welding is 50KHz. Electrolyte is dripped between the positive electrode and the solid electrolyte for wetting. The volume of the electrolyte is 7.5μL, and the area of the Na3V2(PO4)3 electrode plate is 1.1304cm 2 The electrolyte is a mixture of sodium perchlorate, ethylene carbonate, fluoroethylene carbonate and dimethyl carbonate, the concentration of sodium perchlorate in the electrolyte is 1 mol / L, the volume ratio of ethylene carbonate and dimethyl carbonate is 1:1, and the volume ratio of fluoroethylene carbonate in the electrolyte is 5%.
[0058] Preparation method of Na3V2(PO4)3 electrode sheet: Na3V2(PO4)3, conductive carbon black and PVDF in a mass ratio of 8:1:1 are mixed evenly, and then mixed evenly with NMP solvent to obtain slurry, wherein the mass fraction ratio of Na3V2(PO4)3, conductive carbon black and PVDF to the mass fraction of NMP is 200:1, and the mixed slurry is coated on aluminum foil and vacuum dried at 120℃ for 24h. It is cut into discs with a diameter of 12mm for standby use to obtain Na3V2(PO4)3 electrode sheet, wherein the loading amount of Na3V2(PO4)3 electrode sheet is about 1mg cm -2 .
[0059] Figure 3This is a SEM image of the ultrasonic welding interface of the sodium metal foil and the Na-β"-Al2O3 solid electrolyte obtained in this embodiment. From the figure, it can be seen that the metal sodium and the Na-β"-Al2O3 solid electrolyte are tightly bonded.
[0060] Construct a symmetric battery of sodium metal foil / Na-β"-Al2O3 solid electrolyte / sodium metal foil, Figure 4 The AC impedance diagram of the symmetrical battery, the impedance value of the Na-β"-Al2O3 solid electrolyte is A1 = 200Ω, from the figure we can see A2 = 300Ω, the calculated interface impedance between the Na-β"-Al2O3 solid electrolyte and the sodium metal foil is A3 = 50Ω, it can be seen that the interface impedance between the metallic sodium and Na-β"-Al2O3 constructed by the ultrasonic welding process is very small.
[0061] Example 4
[0062] A method for tightly combining an alkali metal foil and a solid electrolyte, wherein the alkali metal foil is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a lithium metal foil, the thickness of the alkali metal foil is 0.2 mm, the solid electrolyte is Na-β"-Al2O3, and the thickness of the solid electrolyte is 1 mm.
[0063] The method for tightly combining the alkali metal foil and the solid electrolyte comprises: welding an alkali metal foil on one side of the solid electrolyte by ultrasonic welding, wherein when welding the alkali metal foil on the solid electrolyte: the alkali metal foil is attached to one side of the solid electrolyte, the ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied, the temperature of ultrasonic welding is room temperature 20 to 25°C, the welding time of ultrasonic welding is 15s, and the ultrasonic frequency of ultrasonic welding is 50KHz.
[0064] Figure 5 This is a SEM image of the ultrasonic welding interface of the lithium metal foil and the Na-β"-Al2O3 solid electrolyte obtained in this embodiment. From the figure, it can be seen that the metal lithium and the Na-β"-Al2O3 solid electrolyte are tightly bonded.
[0065] Construct a symmetric battery of lithium metal foil / Na-β"-Al2O3 solid electrolyte / lithium metal foil, Figure 6 The AC impedance diagram of the symmetrical battery, the impedance value of the Na-β"-Al2O3 solid electrolyte is A1 = 200Ω, from the figure we can see A2 = 440Ω, the calculated interface impedance between the Na-β"-Al2O3 solid electrolyte and the lithium metal foil is A3 = 120Ω, it can be seen that the interface impedance between the metallic lithium and Na-β"-Al2O3 constructed by the ultrasonic welding process is very small.
[0066] Example 5
[0067] A method for tightly combining an alkali metal foil with a solid electrolyte, wherein the alkali metal foil is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a lithium metal foil, the thickness of the alkali metal foil is 0.2 mm, and the solid electrolyte is Na3Zr2Si2PO 12 , the thickness of the solid electrolyte is 1 mm.
[0068] The method for tightly combining the alkali metal foil and the solid electrolyte comprises: welding an alkali metal foil on one side of the solid electrolyte by ultrasonic welding, wherein when welding the alkali metal foil on the solid electrolyte: the alkali metal foil is attached to one side of the solid electrolyte, the ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied, the temperature of ultrasonic welding is room temperature 20 to 25°C, the welding time of ultrasonic welding is 15s, and the ultrasonic frequency of ultrasonic welding is 50KHz.
[0069] Figure 7 The lithium metal foil and Na3Zr2Si2PO4 obtained in this example 12 SEM image of the solid electrolyte ultrasonic welding interface. It can be seen from the figure that the metal lithium and Na3Zr2Si2PO 12 The solid electrolytes are tightly bonded to each other.
[0070] Construction of Li metal foil / Na3Zr2Si2PO 12 Symmetrical battery with solid electrolyte / lithium metal foil, Figure 8 The AC impedance diagram of the symmetrical battery, Na3Zr2Si2PO 12 The impedance value of the solid electrolyte is A1 = 100Ω. From the figure, we can see that A2 = 280Ω. The calculated value of Na3Zr2Si2PO 12 The interface impedance between the solid electrolyte and the lithium metal foil is A3 = 90Ω, which shows that the metal lithium and Na3Zr2Si2PO4 constructed by ultrasonic welding process 12 The interface impedance between them is very small.
[0071] Example 6
[0072] A method for tightly combining an alkali metal foil with a solid electrolyte, wherein the alkali metal foil is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a sodium metal foil, the thickness of the alkali metal foil is 0.2 mm, and the solid electrolyte is Na3Zr2Si2PO 12 , the thickness of the solid electrolyte is 1 mm.
[0073] The method for tightly combining the alkali metal foil and the solid electrolyte comprises: welding an alkali metal foil on one side of the solid electrolyte by ultrasonic welding, wherein when welding the alkali metal foil on the solid electrolyte: the alkali metal foil is attached to one side of the solid electrolyte, the ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied, the temperature of ultrasonic welding is room temperature 20 to 25°C, the welding time of ultrasonic welding is 15s, and the ultrasonic frequency of ultrasonic welding is 50KHz.
[0074] Fig. 9 The sodium metal foil and Na3Zr2Si2PO4 obtained in this example 12 SEM image of the solid electrolyte ultrasonic welding interface. It can be seen from the figure that the metallic sodium and Na3Zr2Si2PO 12 The solid electrolytes are tightly bonded to each other.
[0075] Constructing sodium metal foil / Na3Zr2Si2PO 12 Solid electrolyte / sodium metal foil symmetric battery, Fig.10 The AC impedance diagram of the symmetrical battery, Na3Zr2Si2PO 12 The impedance value of the solid electrolyte is A1 = 100Ω. From the figure, we can see that A2 = 140Ω. The calculated value of Na3Zr2Si2PO 12 The interface impedance between the solid electrolyte and the sodium metal foil is A3 = 20Ω, which shows that the interface impedance between the metallic sodium and Na3Zr2Si2PO4 constructed by ultrasonic welding is 12 The interface impedance between them is very small.
[0076] Constructing sodium metal foil / Na3Zr2Si2PO 12 Solid electrolyte / sodium metal foil symmetric battery, Fig.11 Symmetrical cell at 25℃ at 0.1mA cm -2 The cycle diagram under the current density of , the all-solid-state alkali metal battery has stable voltage and good interface stability during the cycle.
[0077] Constructing sodium metal foil / Na3Zr2Si2PO 12 Solid electrolyte / sodium metal foil symmetric battery, Fig.12 Symmetrical cell at 25℃ at 0.2 mA cm -2 The cycle diagram under the current density of shows that the symmetrical battery has stable voltage and good interface stability during the cycle.
[0078] Example 7
[0079] A fully solid-state alkali metal battery, which is a fully solid-state sodium metal battery, comprises: a positive electrode shell, a nickel foam (diameter 10 mm), a positive electrode, a solid electrolyte, a negative electrode, a nickel foam (diameter 10 mm) and a negative electrode shell, two nickel foams are respectively installed between the positive electrode and the positive electrode shell and between the negative electrode and the negative electrode shell as current collectors, the positive electrode shell and the negative electrode shell used in packaging are 2032 battery shells, the negative electrode is an alkali metal foil, and the negative electrode is connected to one side of the solid electrolyte by ultrasonic welding, the alkali metal foil is a sodium metal foil, the thickness of the alkali metal foil is 0.2 mm, and the solid electrolyte is Na3Zr2Si2PO 12 The thickness of the solid electrolyte is 1 mm, and the positive electrode is a Na3V2(PO4)3 electrode sheet.
[0080] The preparation method of the above-mentioned all-solid-state alkali metal battery includes: welding the alkali metal foil on one side of the solid electrolyte by ultrasonic welding, assembling the positive electrode shell, nickel foam, positive electrode, solid electrolyte, negative electrode, nickel foam and negative electrode shell into an all-solid-state alkali metal battery, wherein when welding the alkali metal foil on the solid electrolyte: stick the alkali metal foil to one side of the solid electrolyte, hold the ultrasonic tool head against the surface of the alkali metal foil and apply ultrasonic waves, the ultrasonic welding temperature is room temperature 20-25°C, the ultrasonic welding time is 25s, and the ultrasonic frequency of the ultrasonic welding is 50KHz. Electrolyte is dripped between the positive electrode and the solid electrolyte for wetting. The volume of the electrolyte is 7.5μL, and the area of the Na3V2(PO4)3 electrode plate is 1.1304cm 2 The electrolyte is a mixture of sodium perchlorate, ethylene carbonate, fluoroethylene carbonate and dimethyl carbonate, the concentration of sodium perchlorate in the electrolyte is 1 mol / L, the volume ratio of ethylene carbonate and dimethyl carbonate is 1:1, and the volume ratio of fluoroethylene carbonate in the electrolyte is 5%.
[0081] Preparation method of Na3V2(PO4)3 electrode sheet: Na3V2(PO4)3, conductive carbon black and PVDF in a mass ratio of 8:1:1 are mixed evenly, and then mixed evenly with NMP solvent to obtain slurry, wherein the mass fraction ratio of Na3V2(PO4)3, conductive carbon black and PVDF to the mass fraction of NMP is 200:1, and the mixed slurry is coated on aluminum foil and vacuum dried at 120℃ for 24h. It is cut into discs with a diameter of 12mm for standby use to obtain Na3V2(PO4)3 electrode sheet, wherein the loading amount of Na3V2(PO4)3 electrode sheet is about 1mg cm -2 .
[0082] Fig.13 The constant current charge and discharge test of the all-solid-state alkali metal battery obtained in this embodiment was carried out at 25°C, the charge and discharge cut-off voltage was 2.5-4V, the current density was 1C, 1C=117mA g -1The first cycle discharge capacity is 110 mAh g -1 , first cycle efficiency 95.27%, discharge capacity 101.5mAh g after 700 cycles -1 , the capacity retention rate is 91%, indicating that it has excellent cycle stability.
[0083] Fig.14 The constant current charge and discharge test of the all-solid-state alkali metal battery obtained in this embodiment was carried out at 25°C, the charge and discharge cut-off voltage was 2.5-4V, the current density was 0.5C, 1C, 2C, 3C, 5C, 1C = 117mA g -1 The discharge capacity is 105.9 mAh g -1 、106.2mAh g -1 、105.3mAh g -1 、102.3mAh g -1 、96.7mAh g -1 ; It shows that it has excellent rate performance.
[0084] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. An all-solid-state alkali metal battery, characterized in that: include: A solid electrolyte, a positive electrode and a negative electrode, wherein the negative electrode is an alkali metal foil, wherein the alkali metal foil is a sodium metal foil, and the negative electrode is connected to one side of the solid electrolyte by ultrasonic welding: the alkali metal foil is attached to one side of the solid electrolyte, and an ultrasonic tool head is pressed against the surface of the alkali metal foil and ultrasonic waves are applied; Wherein, the solid electrolyte is Na3Zr2Si2PO 12 The temperature of the ultrasonic welding is 20 to 25° C. from room temperature, the welding time of the ultrasonic welding is 15 to 60 seconds, and the ultrasonic frequency of the ultrasonic welding is 30 to 80 KHz.
2. The all-solid-state alkali metal battery according to claim 1, characterized in that: The thickness of the alkali metal foil is 0.1-0.5 mm.
3. The all-solid-state alkali metal battery according to claim 1, characterized in that: The thickness of the solid electrolyte is 0.4-2 mm.
